2020
DOI: 10.1002/lary.28988
|View full text |Cite
|
Sign up to set email alerts
|

Time is Money: Relative Value Units and Operative Time in Otolaryngology

Abstract: Objectives Physician compensation for procedures is typically rooted in the work relative value unit (wRVU) system. Operative time is one of the factors that goes into the determination of wRVU assignment. There should be consistency between the wRVU/hr rate, irrespective of average operative time required to perform certain procedures. We investigate if wRVU assignment for otolaryngology procedures adequately accounts for increased operative time. Study Design Retrospective analysis of a surgical database. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The authors suggested that a higher percentage of the national GDP and resources may have been assigned to research and thus accounted for difference in publication trends between countries 4 . Moreover, within the American medical system remuneration is often related to relative value units (RVU) which apportion revenue based on procedure-based time, technical expertise, mental effort, practice expense, and physician liability but neglects research obligations (20). While it is difficult to study, it would be of interest to determine how much clinical, teaching and research responsibilities differ between countries in addition to the above-mentioned factors.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that a higher percentage of the national GDP and resources may have been assigned to research and thus accounted for difference in publication trends between countries 4 . Moreover, within the American medical system remuneration is often related to relative value units (RVU) which apportion revenue based on procedure-based time, technical expertise, mental effort, practice expense, and physician liability but neglects research obligations (20). While it is difficult to study, it would be of interest to determine how much clinical, teaching and research responsibilities differ between countries in addition to the above-mentioned factors.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome measure was operative time as recorded in the ACHQC based on the following categories: 0–59, 60–119, 120–179, 180–239, and 240 + min. Operative time is a key factor in determining justification of more complex codes for operative interventions [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Case selection criteria were based on recent work in urology, otolaryngology, and plastic and reconstructive surgery. [6][7][8]…”
Section: Case and Variable Identificationmentioning
confidence: 99%
“…5 Recent work in the surgical literature has focused on the accuracy of this system in estimating wRVUs and thus physician time and effort. [6][7][8] This is important to understand because RVUs are currently used to calculate Medicare reimbursement directly and are used indirectly by HAND 19 (3) many private payers in their reimbursement schemata. Furthermore, many physicians' pay schedules are linked to their generated wRVUs.…”
Section: Introductionmentioning
confidence: 99%